The Effect of Corpora Luteal Number on Serum Progesterone and Estradiol of Ewes During Luteal Phase of Estrous Cycle and Pregnancy - M. Y. Sumaryadi; W. Manalu (Buletin Peternakan, 1995)
Abstract dalam dalam bentuk hard copy